Implementasi Prinsip Good Governance dalam Manajemen Pelayanan Keuangan Syariah di BMT Islam Berdaya Mandiri - Sri Rahma Dewi; Wika Wahyuni; Nurdesri Juni Amelia; Harapan Tua R.F.S (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2025)
This study analyzes the application of good governance principles in the context of Islamic financial service management at Baitul Maal wat Tamwil (BMT) Islam Berdaya Mandiri Kaitakan. This study uses a qualitative approach with a case study method, collecting data through in-depth interviews, participant observation, and analysis of internal documents. The results of the study show that the five principles of good governance transparency, accountability, responsibility, independence, and fairness have been adequately implemented, albeit with varying degrees of depth. Transparency is realized through routine financial reporting at the Annual Member Meeting, although access to daily information is still limited. Accountability is maintained through internal and external oversight mechanisms from the Cooperative Office, although independent external audits have not been carried out routinely. The institution's responsibility is reflected in its sharia compliance, which is supervised by the Sharia Supervisory Board, and the accuracy of its financial reporting. Independence is realized through a deliberative decision-making process, while fairness is applied in the form of non-discriminatory services and the distribution of financing based on field verification. The findings reveal that the main challenges lie in the digitization of information systems and limited resources for external audits. Overall, the implementation of good governance at BMT has created a governance foundation that is in line with sharia principles and modern public administration values, with room for improvement mainly in the optimization of information technology and institutional capacity building.